Myeloid ATP Citrate Lyase Regulates Macrophage Inflammatory Responses In Vitro Without Altering Inflammatory Disease Outcomes - Verberk, Sanne G. S.; van der Zande, Hendrik J. P.; Baardman, Jeroen; de Goede, Kyra E.; Harber, Karl J.; Keuning, Eelco D.; Lambooij, Joost M.; Otto, Frank; Zawistowska-Deniziak, Anna; de Vries, Helga E.; de Winther, Menno P. J.; Guigas, Bruno; et al. (Frontiers in Immunology, 2021)
Macrophages are highly plastic, key regulators of inflammation. Deregulation of macrophage activation can lead to excessive inflammation as seen in inflammatory disorders like atherosclerosis, obesity, multiple sclerosis and sepsis. Targeting intracellular metabolism is considered as an approach to reshape deranged macrophage activation and to dampen the progression of inflammatory disorders. ATP citrate lyase (Acly) is a key metabolic enzyme and an important regulator of macrophage activation. Using a macrophage-specific Acly-deficient mouse model, we investigated the role of Acly in macrophages during acute and chronic inflammatory disorders. First, we performed RNA sequencing to demonstrate that Acly-deficient macrophages showed hyperinflammatory gene signatures in response to acute LPS stimulation in vitro. Next, we assessed endotoxin-induced peritonitis in myeloid-specific Acly-deficient mice and show that, apart from increased splenic Il6 expression, systemic and local inflammation were not affected by Acly deficiency. Also during obesity, both chronic low-grade inflammation and whole-body metabolic homeostasis remained largely unaltered in mice with Acly-deficient myeloid cells. Lastly, we show that macrophage-specific Acly deletion did not affect the severity of experimental autoimmune encephalomyelitis (EAE), an experimental model of multiple sclerosis. These results indicate that, despite increasing inflammatory responses in vitro, macrophage Acly deficiency does not worsen acute and chronic inflammatory responses in vivo. Collectively, our results indicate that caution is warranted in prospective long-term treatments of inflammatory disorders with macrophage-specific Acly inhibitors. Together with our earlier observation that myeloid Acly deletion stabilizes atherosclerotic lesions, our findings highlight that therapeutic targeting of macrophage Acly can be beneficial in some, but not all, inflammatory disorders.